Audiological and psychological assessment of tinnitus patients with normal hearing - Park, Yelin; Shin, Seung-Ho; Byun, Sung Wan; Lee, Zoo Young; Lee, Ho Yun (Frontiers in Neurology, 2023)
This study was performed to assess identifiable abnormalities in tinnitus patients with normal hearing. The medical records of subjective non-pulsatile tinnitus patients with normal hearing confirmed by conventional pure-tone audiometry who visited our tinnitus clinic between March 2020 and May 2022 were reviewed. The loudness discomfort level (LDL), extended high-frequency hearing loss (EHFHL), summating potential (SP)/action potential (AP) ratio, distortion product otoacoustic emission (DPOAE), thresholds of auditory brainstem response (ABR) wave V, somatic modulation, and psychiatric symptoms, such as anxiety, depression, and stress were evaluated by questionnaires. Decreased LDL (n = 48, 59.8%) was the most frequent finding, followed by EHFHL (n = 29, 35.4%), increased SP/AP ratio (n = 27, 32.9%), psychiatric symptoms (n = 24, 29.3%), decreased DPOAE (n = 17, 20.7%), somatic modulation (n = 8, 9.8%), and increased ABR threshold (n = 3, 3.7%); 75.6% of patients had one or more of these findings. The presence of psychiatric symptoms was independently associated with the Tinnitus Handicap Inventory (THI) score. In conclusion, tinnitus in patients with normal hearing may be accompanied by a combination of various subclinical abnormal audiological findings. However, the presence of psychiatric symptoms alone was independently associated with tinnitus distress.